## solving an eqn matlab

### Mangesh KAle (view profile)

on 21 Oct 2019
Latest activity Edited by Mangesh KAle

### Mangesh KAle (view profile)

on 18 Nov 2019 at 21:30
This question was flagged by Star Strider

### Stephan (view profile)

on 27 Oct 2019

[t,y] = delayed;
% plot results
subplot(3,1,1)
plot(t,y(1,:),'LineWidth',2)
title('G(t)')
subplot(3,1,2)
plot(t,y(2,:),'LineWidth',2)
title('I(t)')
subplot(3,1,3)
plot(t,y(3,:),'LineWidth',2)
title('I1(t)')
%% solve system
function [t,y] = delayed
% parameter values:
p.V1=3;
p.Gin=216;
p.Q=0.5;
p.t1=6;
p.V3=10;
p.T2=50;
p.Eg=180;
p.T1=5;
lags=[p.T1 p.T2];
tf=5;
sol=dde23(@ddemodel,lags,zeros(3,1),[0,tf]);
t=linspace(0,tf,100);
y=deval(sol,t);
function df=ddemodel(~,y,lags)
df = zeros(3,1);
% functions
G=y(1);
I=y(2);
I1=y(3);
f1=@(G) 209/(1+exp(-G/300*p.V3 +6.6));
f2=@(G) 72*(1-exp(-G/144*p.V3));
f3=@(G) 0.01*G/p.V3;
f4=@(I) 90/(1+exp(-1.772*log(I/p.V1) + 7.76)) +4;
f5=@(I) 180/(1+exp(0.29*I/p.V1 -7.5));
df(1) = p.Gin-f2(G)-f3(G)*f4(I)+f5(lags(2));
df(2) =f1(G)-I/p.t1;
df(3) = p.Q*f1(G)-I/p.t1 +(1-p.Q)*f1(lags(1));
end
end
gives the following result:
I think this may be a bit more helpful. If not let me know - but also let me know if it helps...